Implementasi ERP SAP dalam pembuatan report demografi organisasi (Studi kasus PT. Krakatau Steel (Persero) Tbk.) - Ilham Bashirudin; Erlangga Fausa; Amarria Dila Sari (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
The demographics of an organization have a positive influence on organizational commitmentthat ultimately affects the performance of an organization. The absence of such information will result in significant lack of essential information for management in organizational optimization The following journals explain the implementation of SAP ERP in making an organization demographic report, where the use of the software can bypass the drafting process which initially requires a long process and long time (average time 30 minutes) becomes a short process (average time less than 1 minute) or there is a 30x acceleration of time. In addition, there are also benefits of real time output from the hassle of organizational demography. Increasing the speed of report preparation shows that SAP ERP provides great benefits for the organization in running its business processes.